Active Metabolites as Antidepressant Drugs: The Role of Norquetiapine in the Mechanism of Action of Quetiapine in the Treatment of Mood Disorders - Lopez-Munoz, Francisco; Alamo, Cecilio (Frontiers in Psychiatry, 2013)
Active metabolites of some antipsychotic drugs exhibit pharmacodynamic and pharmacokinetic properties that may be similar to or differ from the original compound and that can be translated by a different profile of responses and interactions to clinical level. Some of these antipsychotics’ active metabolites might participate in mechanisms of antidepressant activity, as m-chlorophenylpiperazine (aripiprazole), 9-OH-risperidone and norquetiapine. Norquetiapine exhibits distinct pharmacological activity from quetiapine and plays a fundamental role in its antidepressant efficacy. In this review, we analyze the differential pharmacological aspects between quetiapine and norquetiapine, both from the pharmacokinetic and pharmacodynamic perspectives (affinity for dopaminergic, noradrenegic, and/or serotonergic receptors, etc.), as well as differential neuroprotective role. The pharmacological differences between the two drugs could explain the differential clinical effect, as well as some differences in tolerability profile and drug interactions. The available data are sufficient to arrive at the conclusion that antidepressant activity of quetiapine is mediated, at least in part, by the active metabolite norquetiapine, which selectively inhibits noradrenaline reuptake, is a partial 5-HT1A receptor agonist, and acts as an antagonist at presynaptic α2, 5-HT2C, and 5-HT7 receptors.